2013
DOI: 10.1016/j.antiviral.2013.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The use of sialidase therapy for respiratory viral infections

Abstract: DAS181 is an inhaled bacterial sialidase which functions by removing sialic acid (Sia) from the surface of epithelial cells, preventing attachment and subsequent infection by respiratory viruses that utilize Sia as a receptor. DAS181 is typical of bacterial sialidases in cleaving Sia α2-3 and Sia α2-6 linkages, and it also has a demonstrated effect against acetylated and hydroxylated forms of Sia. The potency of the compound has been enhanced by coupling the active sialidase with an amphiregulin tag, allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 100 publications
2
26
0
Order By: Relevance
“…In summary, inhibiting sialyltransferases is an attractive strategy to investigate the biological roles of sialic acid and potentially treat diseases involving sialic acid recognition, such as autoimmunity (16), cancer metastasis (11), and influenza (36). Although the use of 3F-NeuAc in vivo has some limita-tions, predominantly because of renal failure, the prolonged effect of 3F-NeuAc can be exploited for in vivo experiments, as shown recently by decreased adhesion and migration of cancer cells after in vitro treatment with 3F-NeuAc to block sialylation (43).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, inhibiting sialyltransferases is an attractive strategy to investigate the biological roles of sialic acid and potentially treat diseases involving sialic acid recognition, such as autoimmunity (16), cancer metastasis (11), and influenza (36). Although the use of 3F-NeuAc in vivo has some limita-tions, predominantly because of renal failure, the prolonged effect of 3F-NeuAc can be exploited for in vivo experiments, as shown recently by decreased adhesion and migration of cancer cells after in vitro treatment with 3F-NeuAc to block sialylation (43).…”
Section: Discussionmentioning
confidence: 99%
“…[14]), which has also been applied for influenza virus, could be an approach to inhibit rhinovirus-C and EV-D68 infections. One of the best-described compounds targeting sialic acids is DAS181, a bacterial sialidase that cleaves a2,3and a2,6-sialic acid linkages, and that has been tested in a phase II clinical trial for (para)influenza infection [15,16]. DAS181 also inhibits EV-D68 replication in vitro [17], but it remains to be tested in vivo.…”
Section: Direct-acting Antivirals Entry Inhibitorsmentioning
confidence: 99%
“…The sialidase activity of Fludase cleaves α2,3‐ and α2,6‐linked sialic acid receptors on the cell surface, and their removal prevents influenza virus attachment. Fludase possesses antiviral activity against a broad range of influenza A and B viruses in cell culture and animal models . A phase II study among patients with uncomplicated cases of influenza infection demonstrated significantly reduced viral load and significantly shorter time to sustained decreased viral shedding in the group that received multiple doses of Fludase compared with a placebo group .…”
Section: Challenges Of Meeting the Need For New Antiviral Drugsmentioning
confidence: 99%
“…Fludase possesses antiviral activity against a broad range of influenza A and B viruses in cell culture and animal models. 104 A phase II study among patients with uncomplicated cases of influenza infection demonstrated significantly reduced viral load and significantly shorter time to sustained decreased viral shedding in the group that received multiple doses of Fludase compared with a placebo group. 105 The multidose schedule of Fludase was more effective than the single-dose regimen.…”
Section: What Is In the Drug Pipeline?mentioning
confidence: 99%